Green ICT Assessment for Organisations - Hankel, Albert; Heimeriks, Gaston; Lago, Patricia (Journal of ICT Standardization, 2017)
This study shows how a maturity model on Green ICT can help organisations become more environmentally sustainable in a structured and efficient manner. For this we have used the SURF Green ICT Maturity Model and facilitated the use of this model in four organisations. These organisations participated in a maturity scan, an evaluation session to discuss the results of the scan and a questionnaire on the use of the model. The results show that the model delivers specific suggestions for improvement both on reducing the environmental footprint of ICT and on using ICT as a green solution for business processes. Individual participants reported an increase in awareness on what Green ICT can do.We also looked at whether organisations were ready to use Green ICT and identified potential bottlenecks for further adoption and it was possible to identify such bottlenecks using the results of the maturity scan.